MENGENAI INTERNET SEBAGAI SALAH SATU SUMBER REFERENSI DALAM PENYUSUNAN KARYA TULIS ILMIAH - Desak Putu Eka Nilakusmawati (LPMPP Universitas Negeri Yogyakarta, 2010)
Abstract: A Study on Teachers Knowledge of the Internet as a Reference Sourcefor Scientific Papers. This study aims to investigate the prior knowledge of theteachers of SMPN 3 Tabanan, Tabanan Regency, concerning the internet as one ofthe reference sources for scientific papers and to analyze the effectiveness of trainingin the improvement of their knowledge of ways to search references through theinternet. This study was a pre-experimental study employing the pretest andposttest group design. The data were collected using a pretest and a posttest.Training was conducted on ways to search references for scientific papers,employing presentation and demonstration. The research hypothesis was testedusing a paired sample t-test. The results of the analysis show a t-test value of 14.258(p .01), indicating that the training is effective to improve the participantsknowledge of ways to search references for scientific papers through the internet.Keywords: teachers knowledge, the internet, reference sources